PENGARUH PELAKSANAAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. SEJAHTERA BUANA TRADA CABANG PEKANBARU (KASUS KARYAWAN BAGIAN MARKETING DEALER SUZUKI MOBIL) - Juwita, Ratna; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine the effect of exercise training on the performance of employees of PT. Sejahtera Buana Trada Branch Pekanbaru (Case Employee Suzuki Car Dealer Marketing Division). This research was conducted at PT. Sejahtera Buana Trada Branch Pekanbaru (Suzuki Car Dealer) located in the SM. Amin Number.89 Simpang Baru Tampan. In this research method used is a method of statistical tests with SPSS, where samples were used that employee marketing division of PT. Sejahtera Buana Trada Branch Pekanbaru and as an informant to interview is with the Marketing of PT. Sejahtera Buana Trada Branch Pekanbaru. To determine the sample using census techniques and techniques of data collection by interview and questionnaire. From the results of data analysis include validity, reliability, test T, test R and simple linear regression showed that training has an influence on the performance of employees at PT. Sejahtera Buana Trada Branch Pekanbaru with a value of 0.285 means that the influence of variables of training on employee performance variables was 28.5%. The results of hypothesis testing found that t-count is greater than t-table which means Ha accepted.Keywords: Training and Employee Performance